PENGEMBANGAN INSTRUMEN PENILAIAN NON TES (AFEKTIF DAN PSIKOMOTORIK) DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Halimatus Sadiyah; Moh. Sahlan (As-Sulthan Journal of Education, 2026)
Assessment in Islamic Religious Education (PAI) has long been dominated by test-based instruments that measure only the cognitive domain, while the affective domain (attitudes, morals, religious values) and the psychomotor domain (practical worship skills) remain inadequately measured. This study aims to develop valid and reliable non-test assessment instruments to measure students' affective and psychomotor domains in PAI learning. The study employs a Research and Development (R&D) approach using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The developed instruments include attitude observation sheets, Likert attitude scales, teacher observation journals, self-assessment, peer-assessment, as well as performance assessment sheets and portfolios to measure worship skills such as ablution, prayer, and Qur'anic recitation. Expert validation results indicate that the instruments are suitable for use with a high validity category, and reliability testing shows adequate coefficients for field implementation. The study concludes that systematically developed non-test instruments can complement the limitations of test-based evaluation and provide a holistic picture of students' learning achievement in PAI, while supporting the implementation of authentic assessment within the Merdeka Curriculum.